Kreativitas Guru dalam Meningkatkan Motivasi Belajar Siswa pada Mata Pelajaran PKN - Sri Agustina Sibuea; Ayu Ramadhani; Dini Aprilia; Nur Aqilah Pohan; Amiruddin Amiruddin (Departement of Mathematics Education, 2023)
This research was conducted with the aim of being able to find out the importance of rewards for students learning motivation at SDN 050713 Hinai District, Langkat Regency. This study uses an approach in PKN learning which attempts to increase student learning motivation by giving rewards, as well as the constraints that affect the application of rewards. The design of this study used qualitative methods by making direct observations at SDN 050713, Hinai District, Langkat Regency. And by asking several questions to the class teacher (interview) to get research results or relevant information and data.The results of the study concluded that the teaching and learning process with the role of reward greatly influences the sustainability of the learning process.